STRUCTURAL CRITERIONS OF PROTOAKTIVIZATIONS OF SREDNEPRIDNEPROVSKIY BLOK OF THE UKRAINIAN SHIELD - ZANKEVYCH, B. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Structural positions of dykes of complexs TMA different by age, shown as spesifsc indicators of displacement component of regions tectonic movements of the deep faults of USh.